After the Change of Times: Less Russia in German Foreign Trade - Klaus Schrader (Estonian Discussions on Economic Policy, 2023)
The Russian war of aggression against Ukraine on February 24, 2022, prompted the German government to fundamentally rethink Germany's political and economic relations with Russia. A “change of times” was proclaimed which meant a caesura in foreign and security policy as well as the overcoming of economic dependencies on Russia. This article analyzes whether Germany has substantially reduced its foreign trade relations with Russia more than a year after this proclamation. It is shown that on the German export side, there was no substantial dependence on exports to Russia in any significant sector in the year of war 2022. The loss of importance of trade with Russia had no negative impact on the overall development of German exports. However, the momentum of Russian exports was already broken after the occupation of Crimea in 2014. On the import side, in contrast, a substantial reduction in trade relations did not take place before. Until 2022, dependencies on Russia as a supplier of raw materials remained high, especially in the case of pipeline-bound natural gas with a Russian import share of 55 percent. Germany corrected this political error at high cost and made itself independent of Russian natural gas imports by the end of 2022. – – Der russische Angriffskrieg gegen die Ukraine am 24. Februar 2022 veranlasste die Bundesregierung, die politischen und wirtschaftlichen Beziehungen Deutschlands zu Russland grundlegend zu überdenken. Es wurde eine ,,Zeitenwende“ ausgerufen, die eine Zäsur in der Außen- und Sicherheitspolitik sowie die Überwindung wirtschaftlicher Abhängigkeiten von Russland bedeutete. In diesem Beitrag wird analysiert, ob Deutschland seine Außenhandelsbeziehungen zu Russland mehr als ein Jahr nach dieser Proklamation deutlich reduziert hat. Es wird gezeigt, dass auf der deutschen Exportseite im Kriegsjahr 2022 in keinem bedeutenden Sektor eine wesentliche Abhängigkeit von Exporten nach Russland bestand. Der Bedeutungsverlust des Handels mit Russland hatte keine negativen Auswirkungen auf die Gesamtentwicklung der deutschen Exporte. Allerdings war die Dynamik der russischen Exporte bereits nach der Besetzung der Krim im Jahr 2014 gebrochen. Auf der Importseite kam es dagegen bisher nicht zu einer wesentlichen Reduzierung der Handelsbeziehungen. Bis 2022 blieb die Abhängigkeit von Russland als Rohstofflieferant hoch, insbesondere bei pipelinegebundenem Erdgas mit einem russischen Importanteil von 55 Prozent. Deutschland hat diesen politischen Fehler mit hohem Aufwand korrigiert und sich bis Ende 2022 von russischen Erdgasimporten unabhängig gemacht.
Keywords: F14; F51; 330; Germany; Russia; International Trade; Sanctions